Odpowiedzi

  • Użytkownik Zadane
2009-09-08T08:42:40+02:00
A) (3 1/3) do potęgi 3 razy0,3 do 4 -(-1/2) do 3 razy (1 1/3) do 2 =
=(10/3)do3*(3/10)do4-(-1/8)*(4/3)do2=
=(1000/27)*(81/10.000)-(-1/8)*(16/9)=
=3-(-2/9)=
=3cale2/9

b)(1 1/3) do 3 razy (-3 3/4) do 2 : 3 - (1/3) do 2=
=(4/3)do3*(-15/4)do2:3-(1/9)=
=256/27*225/16:3-1/9=
=3600/27:3-1/9=
=3600/27*1/3-1/9=
=1200/27-1/9=
=1200/27-3/27=
=1197/27=
=44cale 9/27=
=44cale 1/3

C)(-0,3) do 2 : 0,1 - 0,2 do 3 razy (2 1/2) do 2 =
=9/100:1/10-(8/1000)*(5/2)do2=
=9/100*10/1-(8/1000)*(25/4)=
=9/10-2/40=
=9/10-1/20=
=18/20-1/20=
=17/20